CONSIDERATIONS ON THE PRINCIPLE OF EQUALITY IN EUROPEAN LEGISLATION - Daniel FLOREA (Challenges of the Knowledge Society)
Among the numerous issues and wishes that mankind faces in general, the fundamental rights and duties of an individual hold a major place. The inclusion of citizens’ rights and liberties among the most important issues represents not only the result of their great importance but also of their tight connection with the cardinal problems of the world. The concern with the promotion and guarding of citizens’ rights and liberties have gone beyond the traditional limits and borders, as a result of the historical evolution of humanity, especially after WWII, in the attempt to put an end to exploitation, violence, racism, national discrimination and inequality between people. As far legislation is concerned, there are both international and national laws regarding the fundamental rights, liberties and duties. The achievement of the best correlation between these two categories involve the guarantee of citizens’ rights at the levels required by the international laws, which proves to be difficult to put in practice if we take into account the great economic, social and cultural diversity of the world states. The progressive evolution of the constitutional principle and of that of equality depend on the very social reality to which it is supposedly applied; its efficiency will provide the best results only to the extent to which equality becomes the criterion for perfection.